The clinical characteristics and the features of immunophenotype of peripheral lymphocytes of adult onset chronic active Epstein-Barr virus disease at a Tertiary Care Hospital in Beijing. Issue 9 (March 2018) - Luo, Ling; Wang, Huanling; Fan, Hongwei; Xie, Jing; Qiu, Zhifeng; Li, Taisheng
Abstract : Abstract: Chronic active Epstein-Barr virus (CAEBV) infection is a rare disease with high mortality. Most of CAEBV patients have been reported from Japan and are pediatric cases. The goal was to describe the clinical characteristics and the immunophenotypic features of peripheral lymphocytes in adult onset CAEBV patients. We retrospectively reviewed and analyzed all adult onset CAEBV cases admitted to Peking Union Medical College Hospital (PUMCH) between 2012 and 2016. Demographic, clinical, laboratory data, and the immunophentyping data of peripheral lymphocytes were collected. There were 28 adult onset CAEBV patients. The median age was 45 (range, 20–81). Most of the patients presented with fever; splenomegaly; lymphadenopathy and hepatitis. Unlike pediatric cases reported, the manifestations of cardiovascular diseases in our patients were pulmonary arterial hypertension, decreased cardiac function and aorta vasculitis. Prevalence of interstitial pneumonitis in our patients were comparatively higher and prevalence of hypersensitivity to mosquito bites were comparatively lower than that reported by Japan. In this study, CAEBV patients had decreased B cell, NK cell, CD4 cell and CD8 cell counts. The prevalence of low level of B cells, NK cells, CD4 cells was relatively higher than reported ever. Chinese adult onset CAEBV patients have different clinical characteristics and are featured by an immunosuppression status as demonstrated by decreased B cell, NK cell, CD4 cell and CD8 cell.